2014
DOI: 10.1088/0741-3335/56/3/035001
|View full text |Cite
|
Sign up to set email alerts
|

Global geodesic acoustic mode in a tokamak with positive magnetic shear and a monotonic temperature profile

Abstract: The analytical solution for global geodesic acoustic modes (GGAMs) in a tokamak with a positive magnetic shear profile and a monotonic temperature profile is found in the framework of magnetohydrodynamic theory. The axisymmetric eigenvalue problem for perturbed pressure and electrostatic potential is formulated as a recurrent set of equations for poloidal Fourier harmonics. The integral condition for the existence of GGAMs is obtained. It is shown that the traditional paradigm of having a off-axis maximum of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 26 publications
1
22
0
1
Order By: Relevance
“…There are already some experiments on the JIPPT-IIU tokamak [33,34] and T-10 tokamak [35,36] about the global feature of GAM. Furthermore, as the width of the CM peak is narrow, it may be an evidence of the global eigenmode [37][38][39]. We conclude that the CM is a poloidally symmetric (m = 0)…”
Section: The Geodesic Acoustic Mode In the Velocity Fluctuationsmentioning
confidence: 74%
“…There are already some experiments on the JIPPT-IIU tokamak [33,34] and T-10 tokamak [35,36] about the global feature of GAM. Furthermore, as the width of the CM peak is narrow, it may be an evidence of the global eigenmode [37][38][39]. We conclude that the CM is a poloidally symmetric (m = 0)…”
Section: The Geodesic Acoustic Mode In the Velocity Fluctuationsmentioning
confidence: 74%
“…A good general agreement is found in the central region of interest, where the GAM intensity, measured in the experiments, is peaked. On the other hand, the linear dispersion relation 4 can not explain neither the staircase nature (the plateaus) of the frequencies nor the GAM peak splitting that is observed experimentally at the radius positions ρ = 0.922 or ρ = 0.932 (although the presence of GAM eigenmodes has been suggested by simplified analytical models [37,38], whose detailed analysis is out of the scope of this paper). For this reason, we can conjecture Figure 6: Comparison of the experimental GAM frequencies [26] to the numerical values, obtained with the formula given in Eq.…”
Section: Comparison With Experimental Datamentioning
confidence: 81%
“…Analytical work [13] has shown that finite Larmor radius effects lead to the existence of global GAM eigenmodes, which could potentially explain the observations. Analytical work based on MHD [14] also found conditions for the existence of a global GAM. However, for the TCV experiments reported here, the single frequency regime is observed at frequencies below the local GAM frequency, whereas the above-mentioned analytical works predict a global GAM propagating at frequencies above the local GAM frequency.…”
Section: Introductionmentioning
confidence: 93%